El gobierno corporativo como insumo para una buena reputación corporativa - Arbulú, Juan A. (2019)
This essay seeks to define the concepts of corporate reputation, corporate governance and risk management in an institution. Corporate reputation is of vital importance for companies; it can be understood as the image projected to different stakeholders. Corporate governance arises from the need to respond to management difficulties and unethical actions affecting the image and, thus, the profitability of an organization. Therefore, corporate governance will be indispensable for corporate reputation, as it represents an opportunity to analyze values and processes that lead to a better company valuation and image, all of this alongside a fair and equitable treatment. In every business there will be risks of different type and effect. Efficient risk management is, therefore, fundamental. This ranges from its identification and acceptance, to the reduction and control of its effects. The board of directors is in charge of defining an organizational culture focused on risk management. Accordingly, this essay stresses the relevance of “reputational” risk. If this risk is incorrectly handled, a negative result as to corporate reputation would be observed.